Fostering social skills through sociology learning: a mixed-methods study of pre-service social studies teachers - Kahar Mashuri; Yusda Novianti; Masrizal Masrizal (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The development of social skills is a crucial demand in 21st-century higher education, particularly for pre-service teacher students. This study aims to examine the role of sociology learning in the development of social skills among students of the Social Studies Education Program at STKIP Al Maksum involving 15 students in the qualitative phase (in-depth interviews) and 60 students in the quantitative phase (instrument trial).